Chemo-entrepreneurship Modelling on Chemical Bonding Materials as an Effort to Grow Entrepreneurial Spirit of Students with Hearing Impairment in (Islamic) Senior High School - Agus Kamaludin (Universitas Islam Indonesia, 2018)
ABSTRACT: This research aims to develop MEc Bond learning media (Magnetic Educhem Bonding) for students with hearing impairment in (Islamic) senior high school based on chemo-entrepreneurship modeling. This research uses the development model by Borg & Gall that includes the identification of potentials and problems, product selection, literature review, planning, developing initial product draft, initial field trials and product revisions, and it ends with major field trials and product revision. The subjects of this research include material experts, media experts, disability experts, senior high school chemistry teachers and students. The data of this research are taken by using several instruments:interview guide, product quality assessment sheet, and student response sheet. The interview result is analyzed by using descriptive technique, assessment result of product quality is analyzed by using categorical descriptive quantitative technique, and student's response is analyzed by using percentage technique. The results of this research has been developed with the input from the validation specialist and chemistry teachers. Learning media which is developed has best quality, according to the assessment of chemistry teachers in (Islamic) senior high school, with the ideality percentage of 91.02%. In general, students with hearing impairment might respond positively which gets the ideality percentage of 86% to the MEc Bond learning media which makes the material chemical bonds easier to be understood and fun. In addition, the media is desperately necessary for studying chemical bonding in class and it can foster entrepreneurial spirit for the students in the form of making learning media ofchemical bonds.Keywords: chemo-entrepreneurship, learning media, chemical bonds, MEc bondReceived: 16 January 2018, Revised: 31 January 2018, Accepted: 25 February 2018